Feasibility of laparoscopic inguinal hernia repair (TEP) in rural centre in India - Sawarkar, Prashant; Zade, Ranjana; Dhamanaskar, Suchine; Gathe, Bhupendra; Sawardekar, Pradip; Khade, Amol (International Surgery Journal, 2017)
Background: Inguinal hernia repair is one of the most frequently performed operations in general surgery worldwide. Routinely used gold standard Lichtenstein technique gives a long scar and more post-operative pain. TEP has demonstrated favourable short-term results, with regards to reduced postoperative stay, pain and earlier return to physical activity in comparison with open mesh repairs. Methods: This study was prospective observational study in which 75 patients were included for TEP repair and followed for the outcome measured as the time taken for operation, incidence of intra operative and post-operative complications, severity of pain at post-operative day 1, 1 week, 1 month and 6 months after operation, return to work and cost effectiveness of inguinal hernia repair. Results: We have enrolled the 75 patients from 16 to 80 years out of which 34 (45.3%) patients were from age group 50 to 70 years. 47 (62.7%) patients operated on right side and 58 (77.4%) were operated for indirect hernia. Mean time taken for TEP was 81.5 minutes with minimum of 45 minutes and maximum of 135 minutes. There was single most complications of Pneumoperitoneum in 24 (32.0%) which was benign and managed conservatively. Other complications include bleeding in 4 (5.3%) and vas injury in one (1.3%). the mean duration of time taken for return to work was 11 days. The mean cost of TEP was Rs. 5932 with minimum of Rs. 4327 and maximum of Rs. 7742. Conclusions: The laparoscopic (TEP) repair is well established surgery for primary hernia repair and the other open tension free Lichtenstein technique is still regarded as a gold standard for inguinal hernia repair. The laparoscopic hernia surgery attempting similar claims underwent controversies with conflicting results. Laparoscopic (TEP) inguinal hernia repair gives greater patient’s satisfaction and better cosmetic results than open (Lichtenstein) repair.